PEMANFAATAN PRODUK CACAHAN PELEPAH SAWIT SEBAGAI PAKAN ALTERNATIF TERNAK SAPI DI DESA BANYUASIN RIAU SILIP BANGKA - Erwanto, Erwanto; Sukanto, Sukanto; Saputra, Dandi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
One of the superior programs for agriculture, plantations and food crops through the 3S slogan, namely Sahang (pepper), cows and rice fields, which has been established by the Bangka Belitung Islands Provincial Government, and cows are a source of animal protein that people consume every day. The need for beef will increase at certain moments, for example the celebration of Eid al-Fitr, Eid al-Adha or other major holidays. Another superior plantation product that is the focus of plantation farmers in Bangka Belitung is oil palm. From these two agricultural commodities, integration of cattle farming and oil palm plantations can be developed with the aim of getting benefits in the form of cross-utilization of waste from oil palm plantations as additional green feed and manure waste. from cattle farms as organic fertilizer, with the hope of efficiency and mutual benefit. However, there are separate problems for small-scale livestock groups in implementing this program, because to utilize agricultural waste in the form of palm fronds requires a chopping process so that it can be used as a replacement feed source for green food, if done manually it will certainly not be able to meet needs. this feed, and this is an obstacle faced by the Towards Prosperity Farmers Group partners on Jalan Belinyu Silip, Riau Silip sub-district, Bangka Regency. From the problems mentioned above, it can be concluded that appropriate technology is needed to help the process of chopping oil palm fronds into cattle feed products, making it easier to provide cattle feed every day, and it is hoped that this solution can increase the number and income of cattle breeders.